Though Muslims Exist Today, Islam Does Not (American Journal of Islam and Society, 2005)
Comparing the responses of Ariel Cohen to those of John Esposito andGraham Fuller makes it crystal clear that promoting the concept of moderateMuslims accords with our previously described struggle between the twoAmericas: extremism versus ideals. This situation is compounded by theself-contradiction and total confusion of the moderates, who, in their desireto cope with the increasingly unreasonable rather than purely un-Islamicstandards, wish to appease the extremists in power and attempt to present anIslam that is acceptable to both Muslims and non-Muslims alike.Instead of elaborating on the supposed “radical ideologies” spread bythe “Islamists,” the extremists (Cohen) jump to suggesting that they“should not enjoy the constitutional protections of freedom of religion orfree speech.” Still others suggest “in the long term ... the legal activities ofIslamists pose as much or even a greater set of challenges than the illegalones.”1 This is an invitation to open fascism. When a people are not consideredfit even for legal activities, their place in society becomes limited toeither the concentration camp or the gas chamber.The basis of the extremists’ pre-conditions for being a moderateMuslim is the false assertion that Islam is, in the first place, not moderate.Yet an examination of the criteria being referred to by these non-Muslimparagons shows that many points do not contradict Islam, which ensuresthat Muslims are moderate by default. This is aptly shown by their generalrejection of terror attacks on fellow Muslims of whichever school ofthought as well as non-Muslims, whether Christian, Jew, or Hindu. Thus,there is little reason to append moderate to the title Muslim.However, as to the rest of the preconditions employed, these are goodenough to take the Muslim out of the bounds of Islam. To them, for example,moderate Muslims should:1. Not “view the greater Jihad as a pillar of faith, or as a predominantdimension thereof.”22. Accept that “the Koran and the Hadith were written for a time andplace very different from today” and to question the “origins ofIslam.”3 ...